The Potential of Adeno-associated virus Vector Gene Therapy for Achromatopsia - Farianti Wiranda; Grace Marta Tanjung; Yudha Pandapotan; Santi Anugrahsari (Fakultas Kedokteran dan Ilmu Kesehatan Ukrida, 2023)
Achromatopsia, also known as color blindness, is the inability to distinguish certain colors. Where this is the inability of the eye cone cells to capture a certain color spectrum due to genetic factors and certain diseases. Abnormalities in the anatomical structure of the eye located on the retina and inherited recessively. These mutations lead to functional loss and slowly progressive degeneration of the cone photoreceptors. Treatment for color blindness is currently limited to genetic counseling, glasses or colored contact lenses. Genetic therapy methods are currently being developed targeting the retinal organs using recombinant adenovirus vectors. The results of research conducted on animals found an improvement in the function of cone cells so that gene therapy is a promising modality in the future.